Modeling HCV disease in animals: virology, immunology and pathogenesis of HCV and GBV-B infections - Manickam, Cordelia; Reeves, R. Keith (Frontiers in Microbiology, 2014)
Hepatitis C virus (HCV) infection has become a global public health burden costing billions of dollars in health care annually. Even with rapidly advancing scientific technologies, this disease still looms large due to a lack of vaccines and affordable treatment options. The immune correlates of protection and predisposing factors towards chronicity remain major obstacles to development of HCV vaccines and immunotherapeutics due, at least in part, to lack of a tangible infection animal model. This review discusses the currently available animal models for HCV disease, with a primary focus on GB virus B (GBV-B) infection of New World primates that recapitulates the dual hepacivirus phenotypes of acute viral clearance and chronic pathologic disease. HCV and GBV-B are also closely phylogenetically related, and advances in characterization of the immune systems of New World primates have already led to the use of this model for drug testing and vaccine trials. Herein, we discuss the benefits and caveats of the GBV-B infection model and discuss potential avenues for future development of novel vaccines and immunotherapies.